PERANCANGAN DESAIN JARINGAN FIBER OPTIK DENGAN TEKNOLOGI GIGABIT PASSIVE OPTICAL NETWORK DI UNIVERSITAS MALIKUSSALEH - Tjut Adek, Rizal; Yunizar, Zara; Maha, Dedi Torang P; Fajriana, Fajriana (STMIK Palangkaraya, 2022)
Optical fiber is a transmission line that uses glass fibers to transmit light signals from one place to another. Research on FTTH (Fiber To The Home) and FTTB (Fiber To The Building) with GPON (Gigabit Passive Optical Network) carried out on the Malikussaleh University campus by following ITU-T standards. The design process begins with Google Earth mapping, then calculates the feasibility of attenuation, rise time, power link budget, and performs simulations on the Cisco Packet Tracer. Based on the results of the design, the farthest ODP attenuation simulation value is -19,339 dBm and the manual calculation value is 19.2854 dBm, the value meets the ITU-T standard greater than -28 dBm and Telkom is greater than -27 dBm with a power transmitter of 5 dBm, the value of rising Time Budget based on the feasibility of the system, the NRZ limit of 70% or 0.2916ns at the nearest ODP of 0.25 ns and the farthest ODP of 0.2558 ns which can be used because it does not exceed the NRZ limit. Cisco packet router simulation using 3 servers pt, 3 routers, 6 switches, 20 Hups, 20 access points.